Sharing fishers´ ethnoecological knowledge of the European pilchard (Sardina pilchardus) in the westernmost fishing community in Europe - Heitor de Oliveira Braga; Miguel Ângelo Pardal; Ulisses Miranda Azeiteiro (BMC, 2017)
Abstract Background With the present difficulties in the conservation of sardines in the North Atlantic, it is important to investigate the local ecological knowledge (LEK) of fishermen about the biology and ecology of these fish. The ethnoecological data of European pilchard provided by local fishermen can be of importance for the management and conservation of this fishery resource. Thus, the present study recorded the ethnoecological knowledge of S. pilchardus in the traditional fishing community of Peniche, Portugal. Methods This study was based on 87 semi-structured interviews conducted randomly from June to September 2016 in Peniche. The interview script contained two main points: Profile of fishermen and LEK on European pilchard. The ethnoecological data of sardines were compared with the scientific literature following an emic-etic approach. Data collected also were also analysed following the union model of the different individual competences and carefully explored to guarantee the objectivity of the study. Results The profile of the fishermen was investigated and measured. Respondents provided detailed informal data on the taxonomy, habitat, behaviour, migration, development, spawning and fat accumulation season of sardines that showed agreements with the biological data already published on the species. The main uses of sardines by fishermen, as well as beliefs and food taboos have also been mentioned by the local community. Conclusions The generated ethnoecological data can be used to improve the management of this fishery resource through an adaptive framework among the actors involved, in addition to providing data that can be tested in further ecological studies. Therefore, this local knowledge may have the capacity to contribute to more effective conservation actions for sardines in Portugal.